Optimizing Shock Absorber Operation for Improved Hot Forging Efficiency - Meller, Artur; Suszyński, Marcin; Legutko, Stanisław; Trączyński, Marek; Mróz, Adrian; Cernohlavek, Vit (Manufacturing Technology Journal, 2023)
Article presents a novel approach to addressing the challenge of forge-free filling of gas cylinder valve knobs in the context of the pneumatic shock absorber utilized within elevator systems. The shock absorber is a critical component responsible for ensuring accurate and efficient transportation of charge material to the electric inductor of automatic hot forging presses. Precise control of the shock absorber's operation is essential for maintaining proper system functionality and minimizing deficiencies. To investigate the system's response to changes in shock absorber operating parameters, the authors conducted a comprehensive simulation. The simulation results revealed that by identifying specific and optimal operational characteristics, the level of deficiencies can be significantly reduced. These findings offer valuable insights into system behavior, facilitating the optimization of shock absorber operation and overall improvement of the hot forging process. Implementation of the optimized shock absorber operation based on the simulation outcomes can enhance productivity, cost-efficiency, and quality in the hot forging industry.
Keywords: Die forging; Forging defects; Differential equations; Computer algebra system; Computer simulations